Civic Education and Civic Politics: Dimensions, History, and the Formation of Critical Citizens in Indonesia - Rindu Erwin Marpaung; Emanuela Hutabarat; Melisa Apriani Saragih; Rean Frandika Sinaga; Melly Amelia; Siloni Grace Purba; Kalista Silitonga; Dostaria Simbolon (Global Education Journal, 2025)
This article aims to explain the conceptual differences between Civic Education and civic politics, outline the dimensions of citizenship, and trace the development of civic politics in Indonesia since the early 20th century. This article uses a literature study method with a conceptual-historical approach. The sources analyzed include classical and contemporary works on citizenship studies, citizenship theory, and historical studies of civic politics in Indonesia. The results of the study indicate that Civic Education is in the pedagogical realm as a process of forming civic knowledge, values, and skills, while civic politics is in the practical realm as citizens' actions in fighting for recognition, rights, representation, and justice in the public sphere. Citizenship itself is not only related to legal status, but also includes membership, rights, responsibilities, and participation. In the Indonesian context, civic politics develops through three main fields, namely the politics of recognition, the politics of welfare redistribution, and the politics of representation-democracy. Historically, this development can be traced from the national awakening in the early 20th century, continuing through the Old Order, New Order, and Reformation eras. This article emphasizes that the formation of critical citizens requires Citizenship Education that does not stop at the transfer of normative knowledge but moves towards strengthening political awareness and active civic engagement.